ISLAMIC VALUES IN HUMAN RESOURCE MANAGEMENT PRACTICES: A SYSTEMATIC LITERATURE REVIEW - Sahputra, Muhammad Ridho; Adawiyah, Robi'atul (I-Economics, 2025)
This study systematically literature review (SLR) that examines the integration of Islamic values into human resource management (HRM) practices and their influence on organizational behavior. The SLR method is applied to select and analyze empirical articles from recent academic journals relevant to Islamic HRM and Organizational Behavior. The main focus is on how Islamic principles such as trustworthiness, justice, and excellence are implemented in HRM practices, including recruitment, training, development, leadership and employee behavior, such as work commitment, job satisfaction, motivation, and work ethics. Out of 285 articles screened, 14 met the inclusion criteria, with a dominant contextual focus on Indonesia, Malaysia, and the Middle East which growth of Islamic finance, halal industries, and Islamic social institutions has intensified the need for human resource systems. This geographical concentration highlights both the applicability and the current limitation in generalizability of findings. The analysis reveals that Islamic-based HRM fosters a harmonious organizational culture, enhances employee productivity, and strengthens organizational loyalty. Ethical leadership guided by Islamic values is pivotal in promoting sustainable organizational behavior. This study enriches management literature by integrating a religious perspective often overlooked in mainstream HRM and organizational studies. It also provides practical guidance for organizations in Muslim-majority regions to align HRM practices with Islamic values for superior and sustainable performance.